Analysis of Paediatric Clinical Trial Characteristics and Activity Over 23 Years—Impact of the European Paediatric Regulation on a Single French Clinical Research Center - Arnadottir, Johanna; Luc, François; Kaguelidou, Florentia; Jacqz-Aigrain, Evelyne; , the Collaborative CIC1426 Investigator Group; Auvin,; Auvin,; Delorme,; Vantalon,; Lecen,; eux,; Carel,; et al. (Frontiers in Pediatrics, 2022)
As unlicensed or off-label drugs are frequently prescribed in children, the European Paediatric Regulation came into force in 2007 to improve the safe use of medicinal products in the paediatric population. This present report analyzes the paediatric research trials over 23 years in a clinical research center dedicated to children and the impact of regulation. The database of trial characteristics from 1998-2020 was analyzed. We also searched for differences between two periods (1998-2006 and 2007-2020) and between institutional and industrial sponsors. A total of 379 paediatric trials were initiated at our center, corresponding to inclusion of 7955 subjects and 19448 on-site patient visits. The trials were predominantly drug evaluation trials (n= 278, 73%), sponsored by industries (n=216, 57%) or government / non-profit institutions (n=163, 43%). All age groups and most subspecialties were concerned. We noted an important and regular increase in the number of trials conducted over the years, with an increased number of multinational, industrially sponsored trials. Based on the data presented, areas of improvement are discussed: 1) following ethical and regulatory approval, the mean time needed for trial initiation (6.3 and 6.5 months in periods 1 and 2) could be reduced, 2) availability of expert research teams remain insufficient, time dedicated to research attributed to physicians should be organized and recognition of research nurses is required. The positive impact of the European Paediatric Regulation highlights the need to increase the availability of trained research teams, organized within identified multicenter international paediatric research networks.